2015
DOI: 10.1016/j.bbamcr.2015.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of multiple oncogenic signaling pathways by Hsp90 inhibitor alone or in combination with berberine for treatment of colorectal cancer

Abstract: There is a wide range of drugs and combinations under investigation and/or approved over the last decade to treat colorectal cancer (CRC), but the 5-year survival rate remains poor at stages II-IV. Therefore, new, more-efficient drugs still need to be developed that will hopefully be included in first-line therapy or overcome resistance when it appears, as part of second- or third-line treatments in the near future. In this study, we revealed that heat shock protein 90 (Hsp90) inhibitors have high therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 56 publications
0
48
0
Order By: Relevance
“…Here, we found that β‐catenin was cleaved in a caspase‐dependent manner, which in turn reduced β‐catenin transcriptional activity with a consequent downregulation of cyclin D1 and survivin mRNA expression. Interestingly, the suppression of the β‐catenin‐cyclin D1 pathway, together with survivin reduction, has been shown to overcome AUY922 resistance in colorectal cancer cells …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we found that β‐catenin was cleaved in a caspase‐dependent manner, which in turn reduced β‐catenin transcriptional activity with a consequent downregulation of cyclin D1 and survivin mRNA expression. Interestingly, the suppression of the β‐catenin‐cyclin D1 pathway, together with survivin reduction, has been shown to overcome AUY922 resistance in colorectal cancer cells …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the suppression of the β-catenin-cyclin D1 pathway, together with survivin reduction, has been shown to overcome AUY922 resistance in colorectal cancer cells. 38 However, different modulators involved in resistance to HSP90 inhibitors have been investigated in colorectal cancer and HCC cell lines. 39 Recently, Lee et al have reported that the anti-apoptotic protein Mcl-1 plays a key role in sensitizing effects of AUY922 in colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Studies showed that BBR regulated cell cycle and inhibited cell proliferation in multiple cancers. 6,21,22 BBR induced G1 phase cycle arrest in A549 lung cancer cells through inhibition of the expression of Cyclin D1 and Cyclin E1. 21 In addition, a combination of an Hsp90 inhibitor and BBR inhibited cell growth via inhibition of CDK4 expression and modulation of cyclin D1 in colorectal cancer cells.…”
Section: Bbr Inhibits Cell Proliferation Bbr Regulates Cell Cyclementioning
confidence: 95%
“…A side effect of NVP-AUY922 treatment is the upregulation of survivin expression which can contribute to drug resistance. In contrast, when BBR was combined with NVP-AUY922, the growth of the normally resistant cells was reduced which was mediated by miR-296-5p-mediated suppression of the Pin1/beta-catenin/cyclinD1 signaling pathway and inhibition of CDK4 expression [252]. …”
Section: Introductionmentioning
confidence: 99%